2017
DOI: 10.1016/j.btre.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Exopolysaccharide mediated heavy metal removal: A Review on biosynthesis, mechanism and remediation strategies

Abstract: HighlightsCatastrophe of heavy metal pollution in environment is discussed in terms of remediation through bacterial Exopolysaccharide.Biosynthesis of polymer, mechanism of action and metal remediation through polymer has been expounded deeply.Wide range of bacterial cells and their EPS in diverse forms have been critically analyzed.Challenges that still lie in the path of commercialization has been scrutinized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
243
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(280 citation statements)
references
References 87 publications
5
243
0
9
Order By: Relevance
“…We observed an increase in carbohydrate content (0.2 to 89 % considering 1g/l as 100% yield) in cell-free broth up to 30 ppm metal concentration for lead and chromium while, in presence of 40 ppm cadmium, maximum EPS yield was detected (table 2). Metal-induced EPS synthesis has previously reported in various microorganisms [22]. along with an increase in EPS levels (as mentioned above) suggest a significant role of EPS in metal tolerance.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We observed an increase in carbohydrate content (0.2 to 89 % considering 1g/l as 100% yield) in cell-free broth up to 30 ppm metal concentration for lead and chromium while, in presence of 40 ppm cadmium, maximum EPS yield was detected (table 2). Metal-induced EPS synthesis has previously reported in various microorganisms [22]. along with an increase in EPS levels (as mentioned above) suggest a significant role of EPS in metal tolerance.…”
Section: Resultsmentioning
confidence: 92%
“…The interaction might immobilize metal ions. Thus, as suggested by Gupta and Diwan EPS production can be considered as constitutive nonspecific mechanism displayed by microorganisms in the response of heavy metals [22]. [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments; we observed that the YG4 EPS at 0.5 mg/mL concentration could remove 80.94 ± 1.56% uranyl ions from its aqueous solution. The interaction between EPS molecules and metal ions has been ascribed to electrostatic interactions and coordination bond formation (Gupta and Diwan, 2017;Mohite et al, 2017). This property of removing uranyl ions can play an important role in the reduction of uranium-induced nephrotoxicity by either decreasing the absorption and distribution of uranyl ions or increasing the rate of their excretion.…”
Section: Uranium Compounds Dissociate Into Uranyl Ions [(Uo 2 ) 2+mentioning
confidence: 99%
“…It is well known for producing valuable biological compound like carbohydrates, lipids, proteins and pigments [6], and found in diverse habitats including freshwater, marine environment, hot springs, hypersaline localities, cold and arid deserts [7]. Both the types of EPS are composed of carbohydrate and non-carbohydrate constituents like protein, lipid, sulfate, uronic acid and pyruvate [8]. Presence of sulfate and uronic acid in EPS contribute negative charge and provide sticky behavior to the organisms [9], [10].Basically, EPS is involved in protecting the cell from drastic environmental changes [11].…”
Section: Introductionmentioning
confidence: 99%